Inhibition of joint damage and improved clinical outcomes with rituximab plus methotrexate in early active rheumatoid arthritis: the IMAGE trial. Issue 1 (11th October 2010) - Tak, P P; Rigby, W F; Rubbert-Roth, A; Peterfy, C G; van Vollenhoven, R F; Stohl, W; Hessey, E; Chen, A; Tyrrell, H; Shaw, T M
Abstract : Objectives: Rituximab is an effective treatment in patients with established rheumatoid arthritis (RA). The objective of the IMAGE study was to determine the efficacy of rituximab in the prevention of joint damage and its safety in combination with methotrexate (MTX) in patients initiating treatment with MTX. Methods: In this double-blind randomised controlled phase III study, 755 MTX-naïve patients with active RA were randomly assigned to MTX alone, rituximab 2×500 mg + MTX or rituximab 2×1000 mg + MTX. The primary end point at week 52 was the change in joint damage measured using a Genant-modified Sharp score. Results: 249, 249 and 250 patients were randomly assigned to MTX alone, rituximab 2×500 mg + MTX or rituximab 2×1000 mg + MTX, respectively. At week 52, treatment with rituximab 2×1000 mg + MTX compared with MTX alone was associated with a reduction in progression of joint damage (mean change in total modified Sharp score 0.359 vs 1.079; p=0.0004) and an improvement in clinical outcomes (ACR50 65% vs 42%; p<0.0001); rituximab 2×500 mg + MTX improved clinical outcomes (ACR50 59% vs 42%; p<0.0001) compared with MTX alone but did not significantly reduce the progression of joint damage. Safety outcomes were similar between treatment groups. Conclusions: Treatment with rituximab 2×1000 mg in combination with MTX is an effective therapy for the treatment of patients with MTX-naïve RA. CLinicalTrials.gov identifier NCT00299104 .